2022
DOI: 10.1021/acsestengg.2c00027
|View full text |Cite
|
Sign up to set email alerts
|

Variability of NO2/NOx Ratios in Multiple Microenvironments from On-Road and Near-Roadway Measurements

Abstract: An understanding of the spatial distribution of nitrogen dioxide (NO2) in cities is required to improve health impact assessments for NO2 exposure. In this study, 32 702 5 s averaged on-road measurements and 125 hourly near-roadway measurements were used to evaluate the variability of NO2 and nitrogen oxide (NO x ) concentrations in multiple microenvironments during two sampling campaigns (nonholiday and holiday). Microenvironments impacted by heavy-duty diesel vehicles (HDDVs) had large variations in NO2/NO x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For example, the length of wake could be equivalent to only one vehicle height (generally 1.4–3.5 m depending on the vehicle types) when ψ = 90° (i.e., v ≫ u ). In real-world conditions, chasing measurements are usually conducted with a distance of 10–20 m behind the tested vehicles for the sake of safety. , When the vehicle wake length is significantly smaller than the distance between chasing measurements and tested vehicles, it is reasonable to expect errors in the chasing measurements (erroneous measurements). Thus, it is critical to consider the effect of the yaw angle when evaluating the chasing measurements.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the length of wake could be equivalent to only one vehicle height (generally 1.4–3.5 m depending on the vehicle types) when ψ = 90° (i.e., v ≫ u ). In real-world conditions, chasing measurements are usually conducted with a distance of 10–20 m behind the tested vehicles for the sake of safety. , When the vehicle wake length is significantly smaller than the distance between chasing measurements and tested vehicles, it is reasonable to expect errors in the chasing measurements (erroneous measurements). Thus, it is critical to consider the effect of the yaw angle when evaluating the chasing measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, only PM 2.5 exposure was evaluated by the taxi-based measurements in this study. Researchers have found that the concentrations of traffic-related air pollutants (e.g., NO 2 ) on roadways with a large proportion of diesel trucks were significantly higher than those dominated by gasoline cars . However, PM 2.5 generally showed no rapid variations that can be related to the sub-km level microenvironments (i.e., types of roadways). , Thus, aggravated exposure disparities in urban and rural regions that are related to traffic fleet composition would be disclosed if taxi-based measurements are applied to other traffic-related air pollutants (e.g., NO 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…CC BY 4.0 License 2017;Visser et al, 2019),. while the high fraction of NO2 in the no-chemistry run (90 %) has been used in recent studies to compensate for the absence of short-term conversion of NO-to-NO2 (e. g.Kuhn et al, 2023;Xiang et al, 2022).…”
mentioning
confidence: 99%